Flujometría Doppler Anormal de Arterias Uterinas y Predicción de Preeclampsia: Abnormal Doppler Flowmetry of Uterine Arteries and Prediction of Preeclampsia - Gonzales Herrera, Jorge Ronald (2023)
Objective: To determine the diagnostic accuracy of the abnormal Doppler flow of the uterine arteries in the second trimester of gestation, through the sensitivity, specificity, positive predictive value and negative predictive value of the proto-diastolic notch, Resistance Index, S / D Index and Index of Pulsatility to assess the Likelihood Ratio (LR +) and the prediction of the risk of presenting pre-eclampsia. Material and Methods: Longitudinal, prospective cohort study. 669 pregnant women were studied using pulsed Doppler of the uterine arteries and spectral analysis, without taking into account risk selection, 93 presented preeclampsia (13.9%). Results: Sensitivity between 58-71% Specificity 62-95%. Positive predictive value between 20 - 69%. Negative predictive value between 90 - 95%. The best predictor of preeclampsia in this population was the Pulsatility Index with a Sensitivity of 71% and 95% of Specificity and a Positive Likelihood Ratio (LR +) of 13.6. Conclusion: Abnormal Doppler flowmetry of uterine arteries in the second trimester of pregnancy has a good prediction of preeclampsia in a population not selected for risk.